2009
DOI: 10.1021/nl9019616
|View full text |Cite
|
Sign up to set email alerts
|

Nanodroplet Activated and Guided Folding of Graphene Nanostructures

Abstract: We demonstrate by molecular dynamics simulations that water nanodroplets can activate and guide the folding of planar graphene nanostructures. Once the nanodroplets are deposited at selected spots on the planar nanostructure, they can act as catalytic elements that initiate conformational changes and help to overcome deformation barriers associated with them. Nanodroplets can induce rapid bending, folding, sliding, rolling, and zipping of the planar nanostructures, which can lead to the assembly of nanoscale s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
228
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(233 citation statements)
references
References 49 publications
5
228
0
Order By: Relevance
“…DOI: 10.1103/PhysRevLett.118.198002 The physics of liquid droplets in contact with soft or deformable solids, elastocapillarity, is an active subject of research. Between capillary origami and wrinkling instabilities of thin films [1][2][3][4][5][6][7][8][9], the bending, coiling, and winding of slender structures [10][11][12][13][14][15][16], and elasticitymediated propulsion of droplets [17][18][19], there is no shortage of complexity, self-assembly, or beautiful examples of pattern formation in the field. In addition, some recent results have forced us to question familiar concepts of solid-liquid interactions.…”
mentioning
confidence: 99%
“…DOI: 10.1103/PhysRevLett.118.198002 The physics of liquid droplets in contact with soft or deformable solids, elastocapillarity, is an active subject of research. Between capillary origami and wrinkling instabilities of thin films [1][2][3][4][5][6][7][8][9], the bending, coiling, and winding of slender structures [10][11][12][13][14][15][16], and elasticitymediated propulsion of droplets [17][18][19], there is no shortage of complexity, self-assembly, or beautiful examples of pattern formation in the field. In addition, some recent results have forced us to question familiar concepts of solid-liquid interactions.…”
mentioning
confidence: 99%
“…The resulting structures were still essentially two-dimensional. It has been suggested that chemical techniques could be used to create three-dimensional structures from graphene [22], or that nanoscale water droplets might induce graphene sheets to fold up like the petals of a flower [23,24]. However, none of these ideas have yet been demonstrated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…Elastocapillarity, the interplay between surface tension and elasticity, is of fundamental importance in many areas of research including microfluidics [1], self-assembly [2,3,4,5,6], substrate patterning [7,8,9], wetting of fibers [10,11,12,13,14], and biological systems [15,16,17]. One of the simplest geometries -the contact angle a liquid drop makes with a soft solid -has garnered a great deal of interest [7,18,19,20,21,22,23,24,25,26,27,28].…”
Section: Introductionmentioning
confidence: 99%